2015
DOI: 10.1093/jnci/djv098
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Support Framework for Genomically Informed Investigational Cancer Therapy

Abstract: Rapidly improving understanding of molecular oncology, emerging novel therapeutics, and increasingly available and affordable next-generation sequencing have created an opportunity for delivering genomically informed personalized cancer therapy. However, to implement genomically informed therapy requires that a clinician interpret the patient's molecular profile, including molecular characterization of the tumor and the patient's germline DNA. In this Commentary, we review existing data and tools for precision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(153 citation statements)
references
References 45 publications
1
150
0
2
Order By: Relevance
“…40,41 Several other somatic variant classification systems have been recently reported in the literature. [42][43][44][45][46] Although these classification systems are adaptable to the hematologic malignancy context, applying those focused more specifically on drug trials, as well as those focused on variant-level interpretation and classification, poses greater challenges.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Several other somatic variant classification systems have been recently reported in the literature. [42][43][44][45][46] Although these classification systems are adaptable to the hematologic malignancy context, applying those focused more specifically on drug trials, as well as those focused on variant-level interpretation and classification, poses greater challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However, obstacles abound because of the experimental nature of the clinical trials, the lack of a clear targetable drug for the vast majorityof mutations found through large-scale sequencing, and the absence of strong evidence that a particular treatment might actually be effective for an individual patient. TP53 mutations, in particular, are not currently "clinically actionable" (Meric-Bernstam et al 2015); thus, making use of the molecular genetic information, including the tumor status of TP53, to effectively improve patient care remains a challenge in clinical settings. In the not-too-distant future, however, the presence of TP53 mutations may indeed inform targeted therapeutic approaches.…”
Section: Tp53 At the Crossroads Of Clinical Genomics And Cancer Therapymentioning
confidence: 99%
“…These actionable or potentially actionable genomic alterations often include gene amplifications containing well-characterized oncogenes such as MYCN , ERBB2 , ALK , etc. or deletions including certain tumor suppressor genes [Meric-Bernstam et al, 2015]. Identification of these CNVs, together with additional genomic informa- 168 tion revealed by other high-throughput technologies, has created an opportunity for delivering genomically informed personalized therapy.…”
Section: The Role Of Cma In Cancer Genomicsmentioning
confidence: 99%
“…Genomic alteration data on a patient's primary and/or metastatic tumor generated by NGS may qualify patients to enroll in active clinical trials or be treated "off-label or off-protocol" [Meric-Bernstam et al, 2015]. Since genomic testing is revolutionizing the field of cancer therapy, the traditional trial design is also undergoing changes.…”
Section: Clinical Trial Enrollmentmentioning
confidence: 99%